Peran Penyuluh Pertanian dalam Proses Adopsi Inovasi Pupuk Organik pada Kelompok Tani Tirto Mulyo Desa Bumiharjo, Kecamatan Glenmore, Kabupaten Banyuwangi - Mohammad Wahyu Margono; Diah Puspaningrum; Sri Subekti; Sudarko Sudarko (AGRITEXTS: Journal of Agricultural Extension, 2025)
The Role of Agricultural Extension Workers in the Adoption of Organic Fertilizer Innovation in the Tirto Mulyo Farmer Group, Bumiharjo Village, Glenmore Sub-District, Banyuwangi Regency. This study examines the role of agricultural extension workers in supporting the adoption of organic farming. This research is motivated by the need to understand the effectiveness of agricultural extension agents in promoting the adoption of organic fertilizer innovations amid shortages of inorganic fertilizers and declining soil fertility. Therefore, the purpose of this research is to analyze the roles of extension agents at each stage of the innovation adoption process within the Tirto Mulyo Farmer Group in Bumiharjo Village, Glenmore Sub-district, Banyuwangi. A qualitative approach was employed, with informants selected purposively. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings show that the roles of extension agents vary across the stages of innovation adoption. In the knowledge stage, agents acted as facilitators, motivators, dynamicators, and educators, but did not yet function as consultants. The persuasion stage revealed only the facilitator role, while in the decision stage, the agents acted as both motivators and consultants. During the implementation stage, they fulfilled the roles of facilitator, motivator, educator, and consultant, although the dynamicator role remained absent. In the confirmation stage, the facilitator, motivator, and consultant roles were evident, while the dynamicator and educator roles did not appear. This study concludes that the roles of extension agents have not been fully optimized across all stages of adoption. It is recommended that extension agents strengthen their consultant and dynamicator functions—particularly in the early and final stages of adoption—and continually enhance the quality of facilitation and technical assistance.